Brazilian Jeitinho and Culture: An Analysis of the Films Elite Squad 1 and 2 - Moraes, Aline Fábia Guerra de (2016)
Purpose: The present study tried to observe the representations of the Brazilian jeitinho, typical of Brazilian culture, through the analyses of the movies Elite Squad and Elite Squad: The Enemy Within.Originality/Gap/Relevance/Implications: The article corroborates the ongoing debate on the field and offers alternatives for the study of Business Administration, by using film analysis as a technique. It is of utmost importance to evidence that analyses such as this, contribute to Business Administration by, when well situated, aiding in the comprehension of themes and concepts, leading students and readers to obtain new reflexions and new perspectives about the subjects in questionKey methodological aspects: The qualitative character is a methodological landmark of this work, which uses the technique of indirect observation to analyze the films. From the utilization of a reflexive methodology, we were supported by the categorization of the data analyzed, based on the “implications” of jeitinho, present in Massukado-Nakatani, Mussi and Pedroso (2009). For a better perspective of these implications, tables were constructed linking them to specific scenes in the films.Summary of key results: Jeitinho appears in the movies as a notable presence in the Brazilian culture, entering the realm of the organizations, which is the case of the Military Police, the organization presented in the analyses of the films.Key considerations/conclusions: Thus, it was possible to notice peculiarities of the Brazilian culture through the analysis of national productions, contributing, then, to the ongoing debate in the field, trying to offer alternatives to the study of Administration, specially in what concerns the absorption of the national culture in the organizations.